Health and genetic ancestry testing: time to bridge the gap. Issue 1 (December 2017) - Smart, Andrew; Bolnick, Deborah; Tutton, Richard
Abstract Background It is becoming increasingly difficult to keep information about genetic ancestry separate from information about health, and consumers of genetic ancestry tests are becoming more aware of the potential health risks associated with particular ancestral lineages. Because some of the proposed associations have received little attention from oversight agencies and professional genetic associations, scientific developments are currently outpacing governance regimes for consumer genetic testing. Main text We highlight the recent and unremarked upon emergence of biomedical studies linking markers of genetic ancestry to disease risks, and show that this body of scientific research is becoming part of public discourse connecting ancestry and health. For instance, data on genome-wide ancestry informative markers are being used to assess health risks, and we document over 100 biomedical research articles that propose associations between mitochondrial DNA and Y chromosome markers of genetic ancestry and a wide variety of disease risks. Taking as an example an association between coronary heart disease and British men belonging to Y chromosome haplogroup I, we show how this science was translated into mainstream and online media, and how it circulates among consumers of genetic tests for ancestry. We find wide variations in how the science is interpreted, which suggests the potential for confusion or misunderstanding. Conclusion We recommend that stakeholders involved in creating and using estimates of genetic ancestry reconsider their policies for communicating with each other and with the public about the health implications of ancestry information.